DESAIN SATELIT MIKRO UNTUK PENGAMATAN MATAHARI DAN CUACA ANTARIKSA - Fitri Sindy, Denis
The Sun is the main driver of space weather. The Sun continuously emits radiation, a stream of charged particles from the Sun's atmosphere, creating a large magnetic field that extends throughout the Solar System. Then, the magnetic field will interact with the Earth's magnetic field, and the interaction of the magnetic field can trigger geomagnetic storms and ionospheric storms that will disrupt space-based and ground-based technological systems. The dependence of modern life on technology makes solar activity vulnerable to causing huge losses. To study and predict Sun activity continuously requires instruments placed in space, so this final project discusses the design of satellites for observing the sun and space weather. In this final project, the satellite is designed with the mission of detecting, identifying, and monitoring solar activity, especially those that can trigger space weather variability that will affect the Earth's environment by using photometric observation methods at ultraviolet wavelengths. To achieve the mission objectives, the payload on this mission consisted of a telescope with an aperture of 150 mm and a focal length of 1800 mm, as well as a CCD camera with an array size of 2048 x 2048 pixels and an image size of 13,5 ????m x 13,5 ????m. The payload with these specifications produces an image of the Sun with a field of view of 0.88o x 0.88o and a spatial resolution of 1.55" x 1.55" per pixel. Solar observations were carried out in five bandpasses, consisting of 171 ?, 195 ?, 284 ?, 304 ?, and 1700 ?. The mission data consist of real-time and non real-time data. In this mission, four subsystems are designed to support the payload to function in accordance with the mission objectives. Consist of a communication subsystem to communicate between the satellite and the ground station, the Attitude Determination and Control Subsystem (ADCS) to determine attitude and control the attitude of the satellite, the Electrical Power Subsystem (EPS) to generate, store, and distribute energy to all satellite subsystems, and Command and Data Handling (C&DH) to regulate communication between satellite subsystems.